Building the Muhammadiyah Association News Portal in Malang City through Journalism Collaborative - Anang Sujoko; Mega Annisa Insidenta Nuril Huda; Ainun Qisthi Rosyidah; Desi Dwi Prianti (Universitas Muhammadiyah Surakarta, 2026)
This article examines the development of Tunasmalang.id as a local news portal intended to strengthen Muhammadiyah’s public communication ecosystem in Malang City. The program aims to enhance the portal’s journalistic capacity through the implementation of collaborative journalism, addressing key challenges such as limited human resources and the absence of professional news-production skills. Using a participatory approach, the initiative involved newsroom mentoring and the integration of student interns to support reporting processes. The program resulted in measurable improvements in productivity and content diversity, with 115 news articles published over three months across education, socio-economic issues, health, and STEM topics. These outcomes indicate a more structured and consistent news workflow. The findings highlight the potential of collaborative journalism to strengthen Muhammadiyah’s local media by improving content quality, expanding audience engagement, and positioning Tunasmalang.id as an inclusive public information platform.